Rhizosphere effect and salinity competing to shape microbial communities in Phragmites australis (Cav.) Trin. ex‐Steud. Issue 2 (8th September 2014) - Borruso, Luigimaria; Bacci, Giovanni; Mengoni, Alessio; De Philippis, Roberto; Brusetti, Lorenzo
Abstract Rhizobacterial communities associated with Phragmites australis (Cav.) Trin. ex Steud. in a hypersaline pond close to Wuliangsuhai Lake (Inner Mongolia – China) were investigated and compared with the microbial communities in bulk sediments of the same pond. Microbiological analyses have been done by automated ribosomal intergenic spacer analysis (ARISA) and partial 16S rRNA gene 454 pyrosequencing. Although community richness was higher in the rhizosphere samples than in bulk sediments, the salinity seemed to be the major factor shaping the structure of the microbial communities. Halanaerobiales was the most abundant taxon found in all the different samples and Desulfosalsimonas was observed to be present more in the rhizosphere rather than in bulk sediment.